1977
DOI: 10.3758/bf03209192
|View full text |Cite
|
Sign up to set email alerts
|

The imagery effect and frequency discrimination

Abstract: A 300-item list of concrete and abstract nouns with varying frequency of occurrence was presented at a 1-sec rate to 144 subjects under imagery or nonimagery instructions. Subjects were then tested on 72 word pairs homogeneous and heterogeneous with respect to concreteness, where the more frequent member of each pair was to be chosen. Frequency discrimination was found to be a function of relative rather than absolute frequency differences between pair members. In addition, a subjective frequency bias for abst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
1

Year Published

1978
1978
1988
1988

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 19 publications
2
10
1
Order By: Relevance
“…These investigators demonstrated that, although objective background frequency of concrete and abstract words was equated based on available word counts (Kucera & Francis, 1967;Thorndike & Lorge, 1944), college student subjects tended to perceive abstract words as having higher frequencies than concrete words. This phenomenon has since been confirmed in subsequent investigations (Ghatala & Levin, 1976;Goedel & Thomas, 1977) and indicates that "phenomenal" or perceived background frequency indeed differs from objective (word-count) frequency for this subject population, and that matching items on the latter alone may be an insufficient control for frequency differences. Ghatala and Levin (1976) rightfully noted that all previous studies reporting the imagery effect in VDL failed to control for phenomenal frequency and that a confound was apparent.…”
mentioning
confidence: 56%
See 3 more Smart Citations
“…These investigators demonstrated that, although objective background frequency of concrete and abstract words was equated based on available word counts (Kucera & Francis, 1967;Thorndike & Lorge, 1944), college student subjects tended to perceive abstract words as having higher frequencies than concrete words. This phenomenon has since been confirmed in subsequent investigations (Ghatala & Levin, 1976;Goedel & Thomas, 1977) and indicates that "phenomenal" or perceived background frequency indeed differs from objective (word-count) frequency for this subject population, and that matching items on the latter alone may be an insufficient control for frequency differences. Ghatala and Levin (1976) rightfully noted that all previous studies reporting the imagery effect in VDL failed to control for phenomenal frequency and that a confound was apparent.…”
mentioning
confidence: 56%
“…The reasons for our use of a 9-point phenomenal frequency rating scale were twofold. First, words scaled in this manner were readily available from a previous study (Goedel & Thomas, 1977).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A strikingly different hypothesis, also consistent with frequency theory, has been advanced by Goedel and Thomas (1977). Their evidence suggested that both right and wrong high-imagery items actually accrue fewer response-based frequency units than their low-imagery counterparts.…”
mentioning
confidence: 95%